Mounier-Kuhn Syndrome: Anesthetic Experience. (3rd April 2012) - Ushakumari, Deepu Sasikumaran; Grewal, Navneet; Green, Michael
Abstract : Mounier Kuhn syndrome, or congenital tracheobronchomegaly, is an under diagnosed clinical entity with peculiar anatomical and physiological features making anesthetic care challenging. A 58-year-old chronic smoker with history of recurrent pneumonia and bronchiectasis presented for septoplasty. Thoracic imaging revealed a dilated trachea and main bronchi, tracheal and bronchial diverticuli, and chronic bronchiectasis with mediastinal lymphadenopathy. An 8.5 cuffed endotracheal tube (ETT) proved too big for his glottic aperture. An 8.0 cuffed ETT with wet gauze packing yielding an adequate seal. Postoperative continuous positive airway pressure to prevent airway collapse followed awake extubation. Anesthetic concerns include grossly enlarged and weakened airways, inefficient cough mechanisms, presence of tracheal diverticuli, and post operative tracheal collapse. Anesthetic planning includes management of endotracheal cuff size. Small size yields air leak and ineffective ventilation. Large size may lead to mucosal damage. Tube dislodgement, copious secretions, chance of expiratory collapse due to the abnormally dilated and thin airways, and post operative monitoring all must be considered.